Huntingtin phosphorylation governs BDNF homeostasis and improves the phenotype of Mecp2 knockout mice. Issue 2 (8th January 2020) - Ehinger, Yann; Bruyère, Julie; Panayotis, Nicolas; Abada, Yah‐Se; Borloz, Emilie; Matagne, Valérie; Scaramuzzino, Chiara; Vitet, Hélène; Delatour, Benoit; Saidi, Lydia; Villard, Laurent; Saudou, Frédéric; et al.
Abstract: Mutations in the X‐linked MECP2 gene are responsible for Rett syndrome (RTT), a severe neurological disorder for which there is no treatment. Several studies have linked the loss of MeCP2 function to alterations of brain‐derived neurotrophic factor (BDNF) levels, but non‐specific overexpression of BDNF only partially improves the phenotype of Mecp2 ‐deficient mice. We and others have previously shown that huntingtin (HTT) scaffolds molecular motor complexes, transports BDNF‐containing vesicles, and is under‐expressed in Mecp2 knockout brains. Here, we demonstrate that promoting HTT phosphorylation at Ser421, either by a phospho‐mimetic mutation or inhibition of the phosphatase calcineurin, restores endogenous BDNF axonal transport in vitro in the corticostriatal pathway, increases striatal BDNF availability and synaptic connectivity in vivo, and improves the phenotype and the survival of Mecp2 knockout mice—even though treatments were initiated only after the mice had already developed symptoms. Stimulation of endogenous cellular pathways may thus be a promising approach for the treatment of RTT patients. Synopsis: BDNF is one of the most prominent deregulated factors in Rett syndrome, a severe neurodevelopmental disorder. This study reveals that huntingtin phosphorylation stimulates BDNF axonal transport and improves many features in a Rett mouse model, suggesting a possible therapeutic approach. Inducing HTT phosphorylation stimulates axonal transport of BDNF vesicles in Mecp2 ‐deficient neurons. HTT phosphorylation in vivo stimulates BDNF release in the striatum, improving corticostriatal synapse homeostasis in Mecp2 ‐deficient mice. Phospho‐mimetic mutation of HTT or treatment by the calcineurin inhibitor FK506 increases BDNF transport in mice. FK506 improves the phenotype and survival of Mecp2 ‐deficient mice through huntingtin phosphorylation. Abstract : BDNF is one of the most prominent deregulated factors in Rett syndrome, a severe neurodevelopmental disorder. This study reveals that huntingtin phosphorylation stimulates BDNF axonal transport and improves many features in a Rett mouse model, suggesting a possible therapeutic approach.